Investigation of the thiol-disulfide system state of rats with encephalopathy caused by the effect of antituberculous drugs - A. V. Levich; N. O. Skorokhodova; D. H. Zhyvytsia; Yu. V. Prosvetov (Zaporozhye State Medical University, 2019)
Objective. To determine in an experimental study the nature of changes in the status of the thiol-disulfide system of rats with encephalopathy, due to the influence of complex of anti-tuberculosis drugs for the treatment of chemoresistant tuberculosis and the possibility of their drug correction with the use of ademetionine 1,4-butanedisulfonate. Materials and methods. The study was conducted on 30 Wistar rats, which were divided into 3 groups: 10 - intact group, 10 - control group (treated with antituberculosis drugs) and 10 - main group (treated with antituberculosis drugs and ademetionine as means of correcting toxic effects). The state of the glutathione system and the content of homocysteine and nitrotyrosine were investigated. Results. Experimental therapy with ademetionine in rats treated with antituberculosis drugs helps to reduce the intensity of chronic oxidative stress in nerve tissue. The introduction of ademetionine establishes the most optimal ratio between the levels of reduced and oxidized thiol groups, as well as glutathione, which indicates the active mobilization of the thiol-disulfide system and the neutralization of products of free-radical oxidation. Under the conditions of nitrosative and oxidative stress, the studied agents increase the resistance of nervous tissue to the manifestations of intoxication. Thus, one of the links of the neuroprotective effect of ademetionin was its ability to stabilize the thiol-disulfide equilibrium. Conclusions. In the functioning of the glutathione-dependent enzymatic system in the tissues of the brain of rats treated with anti-tuberculosis drugs, there was decreased activity of glutathione s-transferase, glutathione peroxidase and glutathione reductase by 2.0, 1.7 and 2.4 times, respectively. Under the conditions of ademetionin therapy, there was increase by 1.7 times in the reduced intermediates of the thiol-disulfide system - SH-group, and an increase of the level of reduced glutathione by 1.9 times, against the background of a significant decrease in the content of its oxidized form - 1.4 times. The use of ademetionin also led to a decrease of the content of potentially neurotoxic compounds - nitrotyrosine and homocysteine by 1.4 and 1.5 times, respectively in the brain tissues, which increases the resistance of nervous tissue to the effects of intoxication.